2019
DOI: 10.1111/bjh.16329
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis in children with haematological malignancies is a salvageable disease: a report from the Israeli Study Group of Childhood Leukemia

Abstract: Mucormycosis has emerged as an increasingly important cause of morbidity and mortality in immunocompromised patients, but contemporary data in children are lacking. We conducted a nationwide multicentre study to investigate the characteristics of mucormycosis in children with haematological malignancies. The cohort included 39 children with mucormycosis: 25 of 1136 children (incidence 2Á2%) with acute leukaemias prospectively enrolled in a centralized clinical registry in 2004-2017, and an additional 14 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
1
20
0
1
Order By: Relevance
“…17 In the literature review, all series but one reported the highest incidence of mucormycosis during induction therapy, which is in line with our case series. 5,8,9,14,17–20…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 In the literature review, all series but one reported the highest incidence of mucormycosis during induction therapy, which is in line with our case series. 5,8,9,14,17–20…”
Section: Discussionmentioning
confidence: 99%
“…Significant corticosteroid use was defined as an administration of 2 mg/kg/d prednisone or equivalent for at least 10 days in the month before the diagnosis of mucormycosis. 8…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematological malignancy is an important risk factor for mucormycosis [13]. In one study, the incidence of mucormycosis among children with acute lymphoblastic leukemia (ALL) was 2.2% [14]. Acute lymphoblastic leukemia and increasing age were two important risk [15].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review including patients up to 2005 found a mortality of 82.8% of CNS aspergillosis reported before 1990, while that of patients reported after 1990 was 39.5% [83]. In a recent analysis on immunocompromised children suffering from mucormycosis, five out of eight patients (62.5%) with rhino-cerebral involvement died, but it has to be noted that the outcome of invasive aspergillosis is generally better than that of mucormycosis [10,11]. Another analysis of 29 immunocompromised children diagnosed with CNS IMD between 2007 and 2016 reported that the probability of 2-year survival was 48.9% [22].…”
Section: Treatment Recommendationsmentioning
confidence: 99%